Birthing Between the “Traditional” and the “Modern”: DāĪ Practices and Childbearing Women’s Choices During COVID-19 in Pakistan - Ali, Inayat; Sadique, Salma; Ali, Shahbaz; Davis-Floyd, Robbie (Frontiers in Sociology, 2021)
Pregnancy and birth are biological phenomena that carry heavy cultural overlays, and pregnant and birthing women need care and attention during both ordinary and extraordinary times. Most Pakistani pregnant women now go to doctors and hospitals for their perinatal care. Yet traditional community midwives, called DāĪ in the singular and Dāyūn in the plural, still attend 24% of all Pakistani births, primarily in rural areas. In this article, via data collected from 16 interviews—5 with Dāyūn and 11 with mothers, we explore a maternity care system in tension between the past and the present, the DāĪ and the doctor. We ask, what does the maternity care provided by the Dāyūn look like during times of normalcy, and how does it differ during COVID-19? We look at the roles the DāĪ has traditionally performed and how these roles have been changing, both in ordinary and in Covidian circumstances. Presenting the words of the Dāyūn we interviewed, all from Pakistan’s Sindh Province, we demonstrate their practices and show that these have not changed during this present pandemic, as these Dāyūn, like many others in Sindh Province, do not believe that COVID-19 is real—or are at least suspect that it is not. To contextualize the Dāyūn, we also briefly present local mother’s perceptions of the Dāyūn in their regions, which vary between extremely positive and extremely negative. Employing the theoretical frameworks of “authoritative knowledge” and of critical medical anthropology, we highlight the dominance of “modern” biomedicine over “traditional” healthcare systems and its effects on the Dāyūn and their roles within their communities. Positioning this article within Pakistan’s national profile, we propose formally training and institutionalizing the Dāyūn in order to alleviate the overwhelming burdens that pandemics—present and future—place on this country’s fragile maternity care system, to give mothers more—and more viable—options at all times, and to counterbalance the rising tide of biomedical hegemony over pregnancy and birth.